Efeito da ordem de execução do exercício combinado na glicemia, pressão arterial e variabilidade da frequência cardíaca em mulheres pós-menopausadas com Diabetes Mellitus tipo 2 - Garcês, Caroline Pereira (2023)
Introduction: Type 2 Diabetes (T2D) can cause deleterious effects on health, especially in women after menopause. Aerobic and resistance exercises are effective in the treatment and prevention of disease complications; however, the optimal order of performing these exercises in a simultaneous session remains unknown. Objective: This study compared the order of execution of a combined exercise session on glycemia, blood pressure (BP), and heart rate variability (HRV) in postmenopausal women with T2D. Methodology: Clinical, crossover, and randomized trial with 15 postmenopausal women with T2D who underwent three experimental conditions: (I) 30 minutes of aerobic exercise (50 to 60% of reserve heart rate) followed by 30 minutes of resistance exercise (3 sets of 8-12 maximum repetitions) (AR); (II) Resistance exercise followed by aerobic exercise (RA); (III) Resting session (CON). Glycemia was assessed at pre, mid, immediately at the end of exercise, and 20, 40, and 60 minutes after the intervention. BP was assessed pre-intervention and at 20, 40, and 60 minutes after exercise. HRV was assessed pre and at 10, 30, and 50 minutes post-exercise. Results: After the aerobic exercise, the AR session showed a lower glycemic value than the CON session (p=0.01). The AR order showed a lower area under the glycemic curve during exercise compared to RA and CON (p<0.05). Post-exercise, all experimental sessions reduced glycemia (p<0.05), with no difference between conditions (p>0.05). Both exercise sessions reduced systolic BP (p<0.05); however, only the AR order resulted in a reduction in diastolic BP (p=0.01) after exercise. Regardless of the order, exercise sessions reduced time domain indices of HRV (p<0.05). Conclusion: The AR order promoted greater glycemic reduction during exercise and appears to be more effective in reducing BP after exercise; however, without a difference in HRV.